CT features of toxic megacolon: A systematic review. Issue 2 (May 2021) - Eghbali, E.; Akhavi Milani, A.; Shirmohamadi, M.; Hosseinifard, H.
Abstract: Introduction: Toxic megacolon is a rare but life-threatening condition. Diagnosis is made when both systemic toxicity and an enlarged colon are present. We undertook a systematic review of the literature to provide a list of toxic megacolon findings on computed tomography (CT) imaging along with the prevalence rate for each finding. Methods: PubMed, Embase, and Cochrane library were searched. After eligibility screening and quality assessment, the reported CT findings of toxic megacolon with their respective prevalence rates were extracted from the included studies. Pooled prevalence rates were calculated for each finding using random-effects model and inverse variance method. I 2 statistics were used to estimate the heterogeneity. All statistical analyses were performed using R software. P-values less than 0.05 were considered significant. Results: Database search yielded a total of 122 records. Only 2 of these studies were finally selected following two-step eligibility screening. Most common CT features of toxic megacolon and their pooled prevalence rates [95% CI] were: colonic distension (reported in 100% of patients), abnormal haustration 96% [0.75–0.99], peri-colonic fat stranding 87% [0.29–0.99], nodular pseudo polyps 76% [0.52–0.91], multilayered appearance of colonic wall 58% [0.38–0.76], and ascites 57% [0.21–0.87]. Other reported CT features: colonic wall thickening, pleural effusion, accordion sign, small bowel/gastric distension, and segmental colonic wall thinning. Conclusion: and implication for practice: Colonic distension can be accompanied by 10 other findings in CT images of patients with toxic megacolon. Although these findings are not specific, toxic megacolon should be included in the list of differential diagnoses when these findings are present.